Therapeutic Agents for the Treatment of Temporomandibular Joint Disorders: Progress and Perspective - Wu, Mengjie; Cai, Jingyi; Yu, Yeke; Hu, Sihui; Wang, Yingnan; Wu, Mengrui (Frontiers in Pharmacology, 2021)
Temporomandibular joint disorders (TMD) is a common health condition caused by the structural or functional disorders of masticatory muscles and the temporomandibular joint (TMJ). Abnormal mandibular movement in TMD patients may cause pain, chronic inflammation, and other discomfort, which could be relieved by a variety of drugs through various delivery systems. In this paper, we summarized commonly used therapeutic agents in the management of TMD as well as novel bioactive molecules in pre-clinical stage and clinical trials. The emerging therapy strategies such as novel intra-TMJ delivery systems and implants based on tissue engineering are also discussed. This comprehensive review will strengthen our understanding of pharmacological approaches for TMD therapy.